Posłańcy Zeusa, aniołowie i archaniołowie u Porfiriusza z Tyru - Osek, Ewa (Vox Patrum, 2023)
This article is to reconstruct, for the first time in the existing sholarship, the angelology in Porphyry of Tyre (A.D. 233-305), the Neoplatonist who introduced angels and archangels into philosophy. Angels were not found in any philosophical system before Porphyry. My philological analysis of the select fragments from Porphyry’s writings: Homeric Questions on the Iliad, Letter to Anebo, On Abstinence, Commentary on Plato’s Timaeus, Philosophy from Oracles, and testimonies in Augustine’s City of God allows to make the following conclusions. Porphyry divided the angelic hierarchy into three orders, and included them into the world soul structure, analogically to its trichotomy. He placed the supreme angelic order in the fixed stars, the second archangelic order in the planetary spheres, the third order – the so-called ferrymen – in Earth’s atmosphere. The angels and archangels of the celestial spheres coincide with the cosmic gods, whereas the sublunary „ferrymen” step into daemons’s shoes, the so-called mediators in Plato’s Symposium. The angels deliver messeges from cosmic gods and good daemoms, and this is their main function. Divine message, transmitted and echoed by angels, is received only by some chosen people: priests and prophets, to whom Porphyry referred the Homeric formula „Zeus’ messengers”. In constructing his angelology Porphyry might be influenced by esoteric texts of the A.D. second century he studied: Apollo’s hexametric prophecies, the Chaldean Oracles by Julian the Theurgist, On the Nature attributed to Zoroaster.